Traffic control for the improvement of sustainability in freeway networks: a bibliometric analysis. Issue 2 (2020) - Sacone, S.; Pasquale, C.; Siri, S.; Ferrara, A.
Abstract: Sustainability is becoming a key factor in the design and control of traffic systems. In the field of traffic control for freeway networks, the performance criteria explicitly included in traffic control schemes to address sustainability are mainly referred to the reduction of the environmental impact and the decrease of accidents. These control objectives are generally considered together with the conventional goal of traffic control, i.e. the minimization of the total traveling times for drivers. This paper reports a bibliometric study based on keyword counting regarding the research works on freeway traffic control developed to improve sustainability. The main goal of such analysis is to evaluate how the interest of researchers on sustainability-related freeway traffic control has evolved over the last decades and which traffic control measures have been mostly used to address such issues.